An analysis of the Hygiea asteroid family orbital region - Carruba, V. [UNESP] (Oxford University Press (OUP), 2013)
(10) Hygiea is the fourth largest asteroid of the main belt, by volume and mass, and it is the largest member of its family, that is made mostly by low-albedo, C-type asteroids, typical of the outer main belt. Like many other large families, it is associated with a 'halo' of objects, that extends far beyond the boundary of the core family, as detected by traditional hierarchical clustering methods (HCM) in proper element domains. Numerical simulations of the orbital evolution of family members may help in estimating the family and halo family age, and the original ejection velocity field. But, in order to minimize the errors associated with including too many interlopers, it is important to have good estimates of family membership that include available data on local asteroid taxonomy, geometrical albedo and local dynamics. For this purpose, we obtained synthetic proper elements and frequencies of asteroids in the Hygiea orbital region, with their errors. We revised the current knowledge on asteroid taxonomy, including Sloan Digital Sky Survey-Moving Object Catalog 4th release (SDSS-MOC 4) data, and geometric albedo data from Wide-field Infrared Survey Explorer (WISE) and Near-Earth Object WISE (NEOWISE). We identified asteroid family members using HCM in the domain of proper elements (a, e, sin (i)) and in the domains of proper frequencies most appropriate to study diffusion in the local web of secular resonances, and eliminated possible interlopers based on taxonomic and geometrical albedo considerations. To identify the family halo, we devised a new hierarchical clustering method in an extended domain that includes proper elements, principal components PC1, PC2 obtained based on SDSS photometric data and, for the first time, WISE and NEOWISE geometric albedo. Data on asteroid size distribution, light curves and rotations were also revised for the Hygiea family. The Hygiea family is the largest group in its region, with two smaller families in proper element domain and 18 families in various frequencies domains identified in this work for the first time. Frequency groups tend to extend vertically in the (a, sin (i)) plane and cross not only the Hygiea family but also the near C-type families of Themis and Veritas, causing a mixture of objects all of relatively low albedo in the Hygiea family area. A few high-albedo asteroids, most likely associated with the Eos family, are also present in the region. Finally, the new multidomains hierarchical clustering method allowed us to obtain a good and robust estimate of the membership of the Hygiea family halo, quite separated from other asteroids families halo in the region, and with a very limited (about 3 per cent) presence of likely interlopers. © 2013 The Author Published by Oxford University Press on behalf of the Royal Astronomical Society.
Keywords: Celestial mechanics; Minor planets, asteroids: general; Minor planets, asteroids: individual: Hygiea